Imino(silyl)disilenes: application in versatile bond activation, reversible oxidation and thermal isomerization. Issue 25 (4th June 2021) - Holzner, Richard; Porzelt, Amelie; Karaca, Uhut S.; Kiefer, Fiona; Frisch, Philipp; Wendel, Daniel; Holthausen, Max C.; Inoue, Shigeyoshi
Abstract : Use of the Si t Bu2 Me group in imino(silyl)disilenes is crucial: The highly stable disilene 2 provides access to versatile reactivity with various small molecules, whereas selective thermal isomerization yields A2 SiSiB2 type disilene 9 . Abstract : Two novel disilenes of type ABSiSiAB bearing N -heterocyclic imino (A = NI t Bu) and trialkylsilyl (B = Si t Bu3 1, B = Si t Bu2 Me 2 ) groups are reported. The reduced steric demand in 2 results in a highly stable, nonetheless flexible system, wherefore ( E / Z ) isomerization is observed from room temperature up to 90 °C. The proposed isomerization mechanism proceeds via monomeric silylenes in line with experimental results. Despite enhanced stability, disilene 2 retains high reactivity in the activation of small molecules, including H2 . The rare example of a disilene radical cation 7 is isolated and shows reversible redox behavior. White phosphorous (P4 ) selectively reacts with 2 to give the unique cage-compound 8 . Selective thermal rearrangement of 2 at higher temperatures yields the A2 SiSiB2 -type disilene 9 (A = NI t Bu, B = Si t Bu2 Me), which bears characteristics of a zwitterionic and a dative central Si–Si bond. The proposed mechanism proceeds via an initial NHI migration followed by silyl migration.